Numerical and Experimental Investigation of Computed Tomography of Chemiluminescence for Hydrogen-Air Premixed Laminar Flames - Liang Lv; Jianguo Tan; Yue Hu (International Journal of Aerospace Engineering, 2016)
Computed tomography of chemiluminescence (CTC) is a promising technique for combustion diagnostics, providing instantaneous 3D information of flame structures, especially in harsh circumstance. This work focuses on assessing the feasibility of CTC and investigating structures of hydrogen-air premixed laminar flames using CTC. A numerical phantom study was performed to assess the accuracy of the reconstruction algorithm. A well-designed burner was used to generate stable hydrogen-air premixed laminar flames. The OH⁎ chemiluminescence intensity field reconstructed from 37 views using CTC was compared to the OH⁎ chemiluminescence distributions recorded directly by a single ICCD camera from the side view. The flame structures in different flow velocities and equivalence ratios were analyzed using the reconstructions. The results show that the CTC technique can effectively indicate real distributions of the flame chemiluminescence. The height of the flame becomes larger with increasing flow velocities, whereas it decreases with increasing equivalence ratios (no larger than 1). The increasing flow velocities gradually lift the flame reaction zones. A critical cone angle of 4.76 degrees is obtained to avoid blow-off. These results set up a foundation for next studies and the methods can be further developed to reconstruct 3D structures of flames.